Identificação de indicadores de sustentabilidade no contexto da implantação da produção enxuta: um estudo de caso - Pinho, Thiago Carlos Fernando de Moraes Garcia (2016)
Many researchers already discussed the efforts of organizations to improve their processes using lean practices and their concerns not only about operational and financial performance, but also about the environmental aspects of their activities. More recently, a number of sustainability indicator development processes have been initiated within large research projects that aim to design tools for sustainability. The results might be demonstrated by performance indicators and the companies and researchers are using several indicators to measure performance in relation to lean practice applications and sustainable production separately. This research aims to identify a set of indicators to measure the lean practice applications based on the sustainability “Triple Bottom Line” concept and literature review of related researches that already developed indicators to measure the performance related to both of the philosophies. Through the set of indicators identified, an analysis of selected indicators was performed in a multinational automobile company, and this case research was conducted in three different product lines, analyzing its indicators retroactively (2010 and 2011) and after the implementation of lean practices (2012, 2013 and 2014). The focus of the case research was the inter units analysis and the validation of some of the identified performance indicators for all product lines analyzed in this research as well as to verify the possibility to use the sustainable performance indicators on a lean practice application context. A major contribution of this research is the possibility of using the set of indicators (176 identified indicators) in future researches as well as assist the researchers in finding and/or proposing another theoretical framework to measure the results achieved by companies that are implementing lean production.